2010
DOI: 10.1038/nn.2487
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted-in-Schizophrenia 1 (DISC1) regulates spines of the glutamate synapse via Rac1

Abstract: Synaptic spines are dynamic structures that regulate neuronal responsiveness and plasticity. Here we describe a role for the schizophrenia risk factor, Disrupted-in-Schizophrenia 1 (DISC1), in the maintenance of spine morphology and function. We show that DISC1 anchors Kalirin-7 (Kal-7) thereby regulating access of Kal-7 to Rac1 and so controlling the duration and intensity of Rac1 activation in response to NMDA receptor activation in cortical culture as well as in vivo brain. This offers explanation for why R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
443
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 373 publications
(470 citation statements)
references
References 50 publications
21
443
2
Order By: Relevance
“…Because DISC1 is involved in essentially all aspects of neurodevelopment (4-7, 11), and because more than a dozen cytosolic proteins are reported to interact with DISC1 (6, 8,[28][29][30], it is likely that DISC1 acts as a scaffold protein inside neurons, recruiting various signaling components to exert its specific function at different developmental stages. It is therefore not surprising that, in contrast to our results, DISC1 has recently been reported to interact with another RAC1-GEF, Kalirin-7, and to inhibit the RAC1 signaling during dendritic spine morphogenesis (31). Despite the differences, these studies together suggest that mutations of genes involved in the RAC-PAK signaling pathway might cause schizophrenia or other related mental illnesses.…”
Section: Discussioncontrasting
confidence: 99%
“…Because DISC1 is involved in essentially all aspects of neurodevelopment (4-7, 11), and because more than a dozen cytosolic proteins are reported to interact with DISC1 (6, 8,[28][29][30], it is likely that DISC1 acts as a scaffold protein inside neurons, recruiting various signaling components to exert its specific function at different developmental stages. It is therefore not surprising that, in contrast to our results, DISC1 has recently been reported to interact with another RAC1-GEF, Kalirin-7, and to inhibit the RAC1 signaling during dendritic spine morphogenesis (31). Despite the differences, these studies together suggest that mutations of genes involved in the RAC-PAK signaling pathway might cause schizophrenia or other related mental illnesses.…”
Section: Discussioncontrasting
confidence: 99%
“…Kal-7/Rac1 cascade and Rac-1 activation in response to NMDA receptor activation in both neuronal cultures and rat brain in vivo 196 are important for the activitydependent spine morphology and functional plasticity 197 . In addition to schizophrenia, genetic association and rare variants in DISC1 have been associated with autism and Asperger's syndrome 198 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several groups have reproducibly reported that DISC1 is expressed in the glutamatergic postsynapses (10)(11)(12). In primary neuron culture, prolonged DISC1 knockdown results in the synaptic deterioration (decrease in spine density and size) after transient outgrowth in the pathological course (10).…”
mentioning
confidence: 96%